The Construction of Knowledge in the Work of a Tattoo Artist: A Look from the Perspective of Aesthetics - Goi Becker, Rúbia; Alves Pacheco de Campos, Simone; Antonello, Claudia Simone (Organizações & Sociedade, 2021)
The present study analyzes how and what knowledge constitutes the daily work of tattooing in light of the organizational aesthetic approach. For this purpose, the authors explore the theme of knowledge at work by considering the knowledge produced in the daily life of this practice, analyzing the interaction between different knowings, artifacts, and practices. The study used techniques of participant observation and narrative interviews, with data analysis through thematic analysis of narratives. The practice of tattooing consists of six types of knowledge: (a) creation and/or reproduction of the design; (b) doings and sayings related to each practice; (c) manipulation of artifacts; (d) technique; (e) body movement; (f) activation of the human senses. Shedding light on the knowledge of the practice of tattooing brings to the focus of organizational studies the importance of the aesthetic dimension, proposing an alternative for the logical-rational understanding of the organizational context.